“Are you analysing me?” A story completion exploration of having a friend who is becoming a psychotherapist - McPherson, Alan S. (European Journal for Qualitative Research in Psychotherapy, 2022)
Many assumptions and myths about the role and identity of counsellors and psychotherapists persist among the public and within popular culture, often perpetuated by anecdotal experience. In this article, I explore how the therapist role may be viewed by a friend, and how this may both reflect and contribute to public perceptions of therapists. 103 participants from around the world completed an online survey in which they were invited to complete a story andsupply demographic information about themselves. In line with a novel research approach known as Story Completion, participants responded to a story stem, exploring what happens when one friend asks another what it would be like to have a friend who is training as a therapist. Following the elimination of some (incomplete or overly short) responses, quantitative and qualitative data gathered from a total of 83 stories were analysed: the former through statistical analysis, and the latter via Reflexive Thematic Analysis. The findings indicate that while the stereotypical image of a therapist as male and practising psychoanalysis remains widespread, there is greater public awareness of the difficulties and costs that stem from working as a therapist. The stories also shed light on the importance of friendship, along with the special qualities required of people intending to train as therapists. The article ends with some reflections on the value and usefulness of the mixed-methods approach used for this study.